Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Petani Bawang Merah (The Influence of Motivation and Compensation on the Performance of Shallot Farmers) - Oktaviani, Dewi Anggun; Sulistyowati, Retno; Lidyana, Novita (Jurnal Ilmiah Sosio Agribis, 2025)
This study analyzes the influence of motivation and compensation on the performance of shallot farmers in Randuputih Village, Probolinggo. Quantitative methods were used with a sample of 40 farmers who are members of the local Shallot Farmers Group Association. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression. The results showed: Motivation (X1) and compensation (X2) have a significant effect simultaneously on performance (Y) (sig. <0.05; R²=0.459) Partially, both variabels have a positive effect with compensation as the dominant factor (coefficient 0.452). This finding indicates that increasing compensation has a greater impact on farmer performance than motivation. This study recommends the need for policies that focus on improving the compensation system to encourage the productivity of shallot farmers.Keywords: Motivation, Compensation and Farmer Performance.